Analysis of the optimal arm stoke in the backstroke - Ito, S. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The most general armstroke of the backstroke in a present competitive swimming is the so-called S-shaped stroke on a side of the body. The author calculated the optimal stroke in the backstroke with a simplified physical model by fluid dynamic characteristic of a palm obtained by a wind tunnel experiment. As a resut, the optimal stroke path of the maximum efficiency and the maximum thrust were obtained as a driving angle, a tilt angle, and an angle of attack of a hand. The maximum efficiency was obtained in the S-shaped pull stroke on a side of the body, while the maximum thrust was obtained in the I-shaped pull stroke parallel to the body axis.